Theories of History History Read across the Humanities - Kelly, Michael J.; Rose, Arthur (Bloomsbury Academic, 2018)
This book considers 'history' through its supplementary function to the field rather than the ground of a study, bringing new insights into historical thinking and historiography across the humanities. It fosters engagement from around the disciplines in historical thinking and invites historians and philosophers of history to see the impact of their work outside of their own specific fields. Essays in this volume discuss music history, linguistics, dance studies, paintings, film and archaeology. This book is essential reading for those interested in the practice of history, philosophy and the humanities more broadly.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: History / Historiography; History; Electronic books